How to do things with epigenetics: An investigation into the use of metaphors to promote alternative approaches to health and social science, and their implications for interdisciplinary collaboration. (March 2020) - Nerlich, Brigitte; Stelmach, Aleksandra; Ennis, Catherine
Epigenetics is a multifaceted field within genetics and genomics which focuses on discovering mechanisms involved in gene expression and regulation. It came to public attention around the turn of the millennium when the human genome began to be deciphered. Initial findings from epigenetics research held the promise of changing how we think about health and illness, evolution and heredity; speculations about how individuals and populations could begin to control such processes through epigenetics were then picked up in the public realm. In this article we concentrate on two normally distant domains within the public sphere: the advertising of alternative health products and services, and the promotion of alternative approaches to social science, especially around how social science deals with the 'biosocial'. Using insights from social representations theory and methods aligned with metaphor analysis, we investigate the meanings of epigenetics rooted in the use of metaphors and commonplaces that are circulating in current popular parlance and that are used to promote academic theories and ideas as well as tangible products and services. We compare and contrast them and assess their implications for collaborations between natural and social scientists. Our findings reveal some surprising similarities between the metaphors and commonplaces used by advertisers and social scientists, based in large part on the fact that both groups draw on the work of prominent epigeneticists. In both instances some fundamental tenets of mainstream biology are contested, and hopes are created for improving individual or population well-being through the manipulation of epigenetic mechanisms. Both domains share some misunderstandings of epigenetics that might lead to problems with interdisciplinary collaborations between social and natural scientists.